On the integration of an axially symmetric galaxy model. Issue 6 (3rd September 2019) - Navarro, Juan F.
Abstract : A numerical exploration of the escape of a particle from a potential well modeling an axially symmetric galaxy requires the integration of millions of orbits over very long spans of time. In this paper, we propose an integration of the equations of motion of the system by recurrent power series. We prove the convergence of the method, compare the computational time of the recurrent series method against the Dormand‐Prince method, and study the propagation of the truncation errors in the numerical solutions.